2012
DOI: 10.1007/s00442-012-2289-9
|View full text |Cite
|
Sign up to set email alerts
|

Are host–parasite interactions influenced by adaptation to predators? A test with guppies and Gyrodactylus in experimental stream channels

Abstract: Natural populations often face multiple mortality sources. Adaptive responses to one mortality source might also be beneficial with respect to other sources of mortality, resulting in "reinforcing adaptations"; or they might be detrimental with respect to other sources of mortality, resulting in "conflicting adaptations". We explored these possibilities by testing experimentally if the responses of guppies (Poecilia reticulata) to the monogenean ectoparasitic worm Gyrodactylus differed between populations adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 60 publications
3
31
0
Order By: Relevance
“…Although the precise mechanisms will have to be further established, our study adds to the growing body of work that suggests that parasites and predation do not seem to have strong interactive effects on guppies (Gotanda et al, 2013;Pérez-Jvostov et al, 2012;Dargent et al, 2013). We understand the limitations of our lack of replication for any given guppy-Gyrodactylus combination, yet we are confident of our results given that our sympatric infection dynamics closely resemble those of a previous study where strong drainage source effects were also observed (Pérez-Jvostov et al, 2012).…”
Section: Fixed Effectsmentioning
confidence: 51%
See 4 more Smart Citations
“…Although the precise mechanisms will have to be further established, our study adds to the growing body of work that suggests that parasites and predation do not seem to have strong interactive effects on guppies (Gotanda et al, 2013;Pérez-Jvostov et al, 2012;Dargent et al, 2013). We understand the limitations of our lack of replication for any given guppy-Gyrodactylus combination, yet we are confident of our results given that our sympatric infection dynamics closely resemble those of a previous study where strong drainage source effects were also observed (Pérez-Jvostov et al, 2012).…”
Section: Fixed Effectsmentioning
confidence: 51%
“…All fish, regardless of whether or not they were initially infected, were treated with N-cyclopropyl-1,3,5-triazine-2,4,6-triamine (cyromazine; Lice And Anchor Worm Treatment, Ecological Laboratories Inc., U.S.A.) which effectively eliminates Gyrodactylus (Pérez-Jvostov et al, 2012). When no Gyrodactylus were seen on a fish over three consecutive days of visual inspection (as above), the fish was considered parasite-free.…”
Section: Fish Collection and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations